DEVELOPMENT OF INFORMATION SYSTEMS IN LOCAL AUTHORITIES: INTERNATIONAL EXPERIENCE AND UKRAINIAN REALITIES - Khomyn, Oleg (Public Management and Policy, 2025)
Global digitalization and rapid innovation and technological development, against the background of Ukraine’s active European integration progress, determine the relevance of the transformation of the system of regional public administration. The upgrade of the activities of local authorities in the context of the integration and development of modern information systems is seen today as a necessary stage in optimizing management processes and electronic document management, information security guarantees, and improving the provision of administrative services. The article is aimed at analyzing the potential of information systems in the functioning of local authorities in the context of Ukrainian realities and international practice. The study analyzes the main directions of application of innovative possibilities of digital optimization, in particular, improvement of management processes, integration of e-governance, provision of cyber protection of confidential data, simplification of the system of providing administrative services. The role of information systems in local development is substantiated, which consists in providing electronic information, access and provision of e-services as a result of effective digital interaction between local authorities, society and business. The rating by the level of e-participation of European countries close to Ukraine in terms of development is investigated. It considers specificity of development of information systems and e-governance in the context of European countries. It is proved that the implementation of modern information systems in the processes of regional public administration can significantly increase the accuracy and efficiency of management decisions, create conditions for simplifying the analysis of significant amounts of information, reduce the risks of leakage of confidential data. It has been substantiated that the digital transformation of the activities of local authorities is positioned as an integral component of the strategy for the development of territorial communities. In promising scientific research, it is advisable to actualize the development of strategies for adapting the existing resource base and motivating territorial formations to implement information systems.